Book Reviews - Miranda Ferreiro, Marta; Sabuy Sabangu, Paulin; Sanguineti, Juan José; Ivaldo, Marco; Brock, Stephen L. (Acta Philosophica, 2008)
Mariano Artigas, Daniel Turbón, Origen del hombre. Ciencia, filosofía y religión, Eunsa, Barañaín (Navarra) 2007, pp. 183. (M. Miranda Ferreiro) Jacques Bouveresse, Peut-on ne pas croire? Sur la vérité, la croyance et la foi, Agone, Marseille 2007, pp. 286. (P. Sabuy Sabangu) Miguel Pérez De Laborda, Introduzione alla filosofia analitica, Edizioni Università della Santa Croce, Roma 2007, pp. 254. (J. J. Sanguineti) Armando Rigobello, L’apriori ermeneutico. Domanda di senso e condizione umana, Rubbettino, Soveria Mannelli 2007, pp. 104. (M. Ivaldo) Robert Sokolowski, Christian Faith and Human Understanding. Studies on the Eucharist, Trinity, and the Human Person, The Catholic University of America Press, Washington, D.C. 2006, pp. xiii + 317. (S. L. Brock)